New retail formats and interregional poles: Lombardia, Piemonte, Emilia Romagna (Ciudades, 2018)
In this article we present the research “The assessement of the territorial impact of commercial poles: factory outlet centre, multiplex, shopping malls. An interregional approach” realized between 2005 and 2007 by the Departments Architettura e Pianificazione of the Polytechnic of Milan, Interateneo Territorio of the Polytechnic and University of Turin and Department of Economy of the University of Parma. The research project has taken in account the goal of the Regions Lombardia, Piemonte and Emilia Romagna, sponsors of the work, to develop a common approach both for the analysis of the phenomenon and for the experimentation of guidelines for its management. The starting point of the research project is related to the observation of the innovation of the commercial formats and to the way how the Regions have passed specific Acts for its regulation. By means of a research methodology which has allowed to integrate and to represent the territorial characters and the localization of the principal new formats in the three regions, we have found out the sites which can be defined “interregional commercial poles” and have proposed common guidelines for their governance.
Keywords: regional planning; shopping centers; EIA